Decolonising Gender: Stories by, About and with Aboriginal and Torres Strait Islander Women - Rennie, Sandra (The Australian Journal of Indigenous Education, 2017)
‘What is my story? Like you, I have many’, wrote feminist academic Sara Ahmed (Ahmed, 2010, p. 1). She asks, what is yours, what is mine? and begins her story at a table. ‘Around the table a family gathers’, she says, ‘Always we are seated in the same place. . .as if we are trying to secure more than our place’ (Ahmed, 2010, p. 1). In this paper, I draw upon Ahmed's work on willfulness and diversity work in higher education to explore the gendered stories of pathways through university shared with me by Indigenous Australian students. In the stories told in this paper, the table becomes the university space and the family becomes the students. The stories become more than securing place; they are stories which talk of willful resilience, resistance and persistence within that place called higher education. Grounded in my doctoral work with seven female Aboriginal and Torres Strait Islander students, this paper specifically focuses on the gendered nature of such willfulness to consider the ways in which Indigenous Australian students negotiate pathways and success through university within/against Western colonial and patriarchal institutions.